(untitled) (Applied Biological Research, 2026)
Phytsyhthesized nanoparticles from different medicinal plants are currently exploited for large scale biomedical applications. The biosynthesis of silver nanoparticles (AgNPs) was carried out by using the aqueous extract of Vitex leucoxylon bark and its properties evaluated by UV-vis spectroscopy, FTIR, and XRD analysis. Also, the antimicrobial, cytotoxic, and antioxidant properties of biosynthesized AgNPs were assessed using standard methods. A characteristic surface plasmon resonance peak at 435 nm, observed in UV visible spectrum, confirmed the formation of V. leucoxylon bark aqueous extract-based AgNPs (Vl-AgNP). The peaks in FTIR analysis showed the presence of several organic constituents that acted as capping and reducing substances. XRD measurements confirmed that Vl-AgNPs were crystalline face-centred cubic structures. DLS analysis of synthesized AgNPs showed a mean hydrodynamic diameter of 177.6 nm with low polydispersity (0.090) and high colloidal stability (−82.8 mV). SEM-EDX analysis showed it to be uniformly distributed Vl-AgNP, while TEM analysis revealed spherical nanoparticles of 50 to 64 nm size. The Vl-AgNPs demonstrated substantial anti-bacterial activity towards human pathogenic bacteria and strong antioxidant activity in dose-dependent manner with maximum inhibition against Escherichia coli. Antioxidant activity showed dose-dependent radical scavenging activity, reaching 77.42 ± 1.25% in DPPH assay at 100 µg mL-1, while FRAP analysis demonstrated moderate reducing power. In vitro cyto toxicity studies using the MTT assay revealed dose-dependent inhibition of HeLa cellsline with an IC₅₀ value of 74.38 µg mL-1. These findings confirm the notable bioactivity of Vl-AgNPs, highlighting their potential biomedical applications.